Integrated Urban River Corridors: Spatial design for social-ecological resilience in Bucharest and beyond - Forgaci, Claudiu (A+BE | Architecture and the Built Environment, 2018)
The issue of urban resilience concerns a multitude of urban systems and spaces. This thesis focuses on Urban River Corridors (URCs)—that is, urban spaces where the overlap between the urban systems (carrying the ’social-‘) and the river system (carrying the ‘-ecological’) is at the highest intensity—as strategic spaces with a potentially high contribution to urban resilience. The general hypothesis is that with an integrated spatial understanding, planning and design of rivers and the urban fabric surrounding them, cities could become more resilient not just to flood-related disturbances, but to general chronic stresses as well. Hence, the thesis addresses four spatial problems arising from the loss of synergy between the natural dynamics of rivers and the spatial configuration and composition of urban areas that they cross: (1) river-taming operations combined with riverside traffic corridors have weakened the relationship between fluvial geomorphology and urban morphology, transforming rivers into physical barriers; (2) flood-protection measures aiming for resistance to water dynamics have led to a latent flood risk; (3) the capacity of urban rivers to deliver ecosystem services has been diminished; and (4) rationalisations of the river system have reduced the scalar, (and implicitly) social and ecological complexity of urban rivers. Drawing on theories of social-ecological resilience and urban form resilience, on conceptual and analytical tools from spatial morphology and landscape ecology, and on practical experience in urban river design projects, the thesis constructs a theory of social-ecologically integrated Urban River Corridors, in which it proposes a spatial-morphological definition, an assessment framework, and a set of design principles and design instruments. Framed as a transdisciplinary design study, the thesis integrates knowledge from various disciplines dealing with the problematique of urban rivers and employs a design-driven methodology that includes design explorations and design testing in the research process. The case of Bucharest crossed by URC Dâmbovița and URC Colentina is used to contextualise the spatial-morphological definition, and to demonstrate, develop and test the proposed assessment framework, design principles, and design instruments with a distinct set of methods in each of the three parts of the thesis. In addition to a transdisciplinary literature review of URCs, and a historical review of Bucharest’s URCs, Part 1 presents a qualitative data analysis of 22 expert interviews, used to determine the current state of URC Dâmbovița and URC Colentina. Based on four key properties of URCs identified in the literature, Part 2 develops an indicator system and a method for the assessment of social-ecological integration. Informed by key problems and potentials identified by the local experts, the assessment framework is then applied on the two URCs of Bucharest. In the last part, design applications, including urban river projects carried out by the author on other rivers and a design workshop in Bucharest, are used to demonstrate and test the design principles through design instruments.